Faktor-Faktor Dalam Meningkatkan Pengungkapan Green Banking - Nada Khamilia; Wahyudin Nor (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
The purpose of this study was to examine and analyze the influence of Operational Cost of Operating Income (BOPO), Capital Adequacy Ratio (CAR), Financial Slack, Human Resource Slack, Sustainability Officer, and Sustainability Committee on green banking disclosure and also to analyze the differences between green banking disclosure before and after the issuance of POJK Number 51 / POJK.03 / 2017 concerning sustainable finance of 12 sample companies of bank sub-sectors listed on the IDX during the 2016-2019 period. The analysis used in this study was multiple linear regression analysis to examine the causality relationship between independent variables on green banking disclosures, as well as the Wilcoxon test to determine differences in the level of disclosure before and after POJK Number 51/POJK.03/2017 issuance. The results of this study indicate that there are differences in green banking disclosures before and after the issuance of POJK Number 51 / POJK.03 / 2017. In addition, it was also found a positive significant effect of the sustainability committee on green banking disclosure while Operational Costs on Operating Income (BOPO), Capital Adequacy Ratio, Financial Slack, Human Resource Slack, and Sustainability Officer have no significant effect.